17.2: KANSEI Evaluation of Color Images Presented in Color Gamuts with Different Blue Primaries. Issue 1 (June 2015) - Ayama, Miyoshi; Fuseda, Takashi; Hamano, Toshiya; Ishikawa, Tomoharu
Abstract : To investigate the best blue primary for color display from KANSEI‐evaluation point of view, evaluation experiment using Semantic Differential method was carried out using four different blue primaries of 430nm, 450nm, 470nm, and 480nm at 60cd/m 2 . The same experiment was done for 450nm, 470nm, and 480nm at 170cd/m 2 . In the results of 4 primaries, 450nm and 470nm blue primaries show the best, 430nm is the next, and 480nm blue primary shows the worst performance. In the results of 3 primaries, 470nm shows the highest scores for bluish test images. Results are compared with color naming data in the entire chromaticity diagram.